Fish functional traits are affected by hydrodynamics at small spatial scale. (February 2016) - Bracciali, C.; Guzzo, G.; Giacoma, C.; Dean, J.M.; Sarà, G.
Abstract: The Mediterranean damselfish Chromis chromis is a species with a broad distribution found both in the Mediterranean Sea and Eastern Atlantic as far south as the coast of Angola. We hypothesized that the species may have significant functional morphological plasticity to adapt along a gradient of environmental conditions. It is a non-migratory zooplanktivorous species and spends the daytime searching for food in the middle of the water column. Therefore, local hydrodynamics could be one of the environmental factors affecting traits of C. chromis with repercussions at the population level. We compared the body condition, individual growth and body shapes of damselfish collected under two different hydrodynamic conditions (low ∼10 cm s −1 vs. high ∼20 cm s −1 ). Specimens showed higher body condition under high-hydrodynamics, where conditions offered greater amounts of food, which were able to support larger individuals. Individuals smaller than 60-mm were more abundant under low-hydrodynamics. Morphometric analysis revealed that high-hydrodynamics were favored by fish with a more fusiform body shape and body traits developed for propellant swimming. Highlights: Local hydrodynamics elicits different patterns of food availability and affects functional traits of a fish on a short scale. Mediterranean damselfish spends the daytime searching for food. Local micro-conditions may have rebounds on fitness. Higher body condition are favored by high-hydrodynamics with greater amounts of food to support larger individuals.